2021
DOI: 10.3390/vaccines9080885
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of COVID-19 Vaccines in Chronic Kidney Disease and Kidney Transplantation Patients: A Narrative Review

Abstract: The SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) pandemic has posed a huge threat to global health because of its rapid spread and various mutant variants. Critical illness occurs in the elderly and vulnerable individuals, such as those with chronic kidney disease. The severity of SARS-CoV-2 infection is associated with the severity of chronic kidney disease (CKD)and even kidney transplantation (KT) because of the chronic use of immunosuppressive agents. To develop adaptive immunity against SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 94 publications
(84 reference statements)
4
55
0
3
Order By: Relevance
“…Hyporesponse to vaccines in general has been described in dialysis patients, in vaccination against hepatitis B, which shows a seroconversion of only 40-70% compared to more than 95% in healthy controls (20), attributing associated factors such as age, the presence of diabetes, nutritional status and altered innate and adaptive immune response (21). However, in our experience, the level of seroconversion with the two Sputnik V components was, on the contrary, much higher, and has already been described with other COVID-19 vaccines in dialysis patients (19,(21)(22)(23)(24)(25)(26), thus highlighting the importance of a complete vaccination in this patients (19,26). Besides, patients who presented COVID-19 after the first Sputnik V component had mild forms of the disease, as has been seen in the general population (27).…”
Section: Discussionsupporting
confidence: 64%
“…Hyporesponse to vaccines in general has been described in dialysis patients, in vaccination against hepatitis B, which shows a seroconversion of only 40-70% compared to more than 95% in healthy controls (20), attributing associated factors such as age, the presence of diabetes, nutritional status and altered innate and adaptive immune response (21). However, in our experience, the level of seroconversion with the two Sputnik V components was, on the contrary, much higher, and has already been described with other COVID-19 vaccines in dialysis patients (19,(21)(22)(23)(24)(25)(26), thus highlighting the importance of a complete vaccination in this patients (19,26). Besides, patients who presented COVID-19 after the first Sputnik V component had mild forms of the disease, as has been seen in the general population (27).…”
Section: Discussionsupporting
confidence: 64%
“…The results of our previous studies also showed a significant humoral post-vaccination response in the vast majority of dialyzed patients [5,6]. In contrast, kidney transplant recipients (KTR) demonstrated a markedly impaired seroconversion rate of 40-60% after two doses of mRNA vaccines [7][8][9]. Liver, heart, and lung transplant recipients exhibited a reduced response to mRNA-based vaccines as well [10][11][12].…”
Section: Introductionmentioning
confidence: 73%
“…However, a recent clinical trial reported that Astrazeneca is well tolerated in the older aged population and produced similar immunogenicity results ( Ramasamy et al, 2021 ). A systemic review showed that the older aged population were usually excluded in most clinical trials of COVID-19 vaccines, leading to insufficient data to analyse vaccine efficacy ( Hou et al, 2021 ). The involvement of gut dysbiosis in inefficacy of COVID-19 in the older age groups warrants extensive studies.…”
Section: Intestinal Dysbiosis Linking Risk Factors To Inefficacy Of Covid-19 Vaccinesmentioning
confidence: 99%
“…It may be necessary to distinguish mild and severe liver diseases on vaccine efficacy ( Cornberg and Eberhardt, 2021 ). A study reported that chronic kidney disease was associated with decreased vaccine efficacy ( Hou et al, 2021 ) due to the uremic milieu- vitamin D deficiency- and insufficient erythropoitin-caused antigen presenting cell dysfunction and reduced B cell numbers. Both a uremic milieu and vitamin D deficiency are known to cause gut dysbiosis ( Chaves et al, 2018 , Chen et al, 2021 ).…”
Section: Intestinal Dysbiosis Linking Risk Factors To Inefficacy Of Covid-19 Vaccinesmentioning
confidence: 99%